2011
DOI: 10.1093/ejcts/ezr170
|View full text |Cite
|
Sign up to set email alerts
|

Improved cardiopulmonary exercise function after modified Nuss operation for pectus excavatum

Abstract: Patients with pectus excavatum have lower cardiac index at submaximal exercise when compared with healthy age-matched controls. Their cardiac index and FEV(1) are increased one year after the modified Nuss operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 16 publications
2
44
1
1
Order By: Relevance
“…The [9][10][11]13], that is, the excavated deformity is repaired without any type (wedge or transversal) of the sternotomy and cartilages resection [12] of abnormally developed parts of the ribs and in another 27 (36%) patients the PE deformation was corrected by modification of D. Nuss procedure and the small statistical validity (P<0.05) was determined between two groups. The patients were distributed by correction method, which is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The [9][10][11]13], that is, the excavated deformity is repaired without any type (wedge or transversal) of the sternotomy and cartilages resection [12] of abnormally developed parts of the ribs and in another 27 (36%) patients the PE deformation was corrected by modification of D. Nuss procedure and the small statistical validity (P<0.05) was determined between two groups. The patients were distributed by correction method, which is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Other than vomiting caused by inadequate dissection, surgical wound infection is a possible postoperative complication after open pyloromyotomy for hypertrophic pyloric muscle (5)(6)(7)(8)(9)11,17,18,27). The incision methods used in open pyloromyotomy that influence the incidence of surgical wound infection include right-upper quadrant horizontal incision and supraumbilical incision as well as whether pyloromyotomy is performed intra or extra-corporeally (12,15,28,29). No authors report the presence of specific postoperative complications after laparoscopic surgery.…”
Section: ■ Explanationmentioning
confidence: 99%
“…Among the articles selected for these guidelines, there are no meta-analyses, RCTs, or non-randomized prospective controlled trials that provide high-level evidence. There is only an analytic epidemiologic study including Nissen fundoplication (27) as well as a descriptive study of Toupet fundoplication (28). The analytic epidemiologic study (27) investigated laparoscopic fundoplication performed for children without neurologic disorders and reports that Nissen and Toupet fundoplication show no difference with respect to the incidence of intraoperative or postoperative complications, postoperative dysphagia, or reoperation.…”
Section: ■ Explanationmentioning
confidence: 99%
“…However, recent studies have refuted this statement and shown physiological improvement after surgical correction in the form of improved cardiac function (8)(9)(10), chest wall motion (11), and lung function (12). Nonetheless, cosmetic complaints are still the main indication for patients to undergo correction (13).…”
Section: Introductionmentioning
confidence: 99%